SENSITIVITY AND RESISTANCE OF ANTIBIOTICS IN COMMON INFECTION OF MALE AND FEMALE - Khurshid, Rukhshan; Sheikh, Mubbashir A; Karim, Sabiha; Munnawar, Farida; Wyne, Humairah (Journal of Ayub Medical College Abbottabad, 2002)
Background: There is increasing concern regarding antimicrobial resistance in Pakistan. Data are limited on the prevalence, pattern of resistance and risk factors associated with resistant organisms. This Study was done to address these issues as they relate to common infection of male/female. Methods: Different clinical materials collected from 100 patients admitted in hospital or who attended out door clinic were used. Antibiotics like Enoxabid, Fortum, Ceporex, Klaricid, Maxaquin, Zenacef, Ceporexin, Urixin, Septran, Keflex, Erythrocine, vibramycin and tetracycline were used for culture sensitivity. Results: It was observed that most of the pus specimens received are from females and urine specimens from males. Specimen of pus contains mostly Staph aureus, Urine specimen contain mostly E.coli whereas Pseudomonas pyrogenosa and proteases were also observed in urine, pus, sputum and ascitic/pleural fluids of patients. Among all drugs that were used, Enoxabid, Ceporex were vary sensitive against strains of Staph and Pseudomonas present in specimen. Strains of proteases were resistant against these drugs. Urixin and Septran show mixed action. In comparison of Enoxabid, Ceporex and Ceporexin, Zenocef and Fortum show sensitivity in fewer cases of Staph and E.coli. Mexaquin shows a good sensitivity against Pseudomonas and E.coli. It was observed that Septran, Erythrocine, Vibramycin, Tetracyclin, Klaracid and Keflex are not very good acting drugs in infection of urine, pus, sputum and fluids. Finding of a low but definite level of resistance to septran, erythrocine, Vibramycin, Tetracyclin, Klaracid and Keflex is important for selection of empiric therapy for infection.